ANALISIS METODE ISTINBATH HUKUM MUHAMMADIYAH DAN NAHDLATUL ULAMA TERKAIT PEMBELIAN KREDIT - Marzuki; Imdadun, Muhammad; Pujiharto, Yaya Ruhenda Casmita (Institut Agama Islam Sahid Bogor, 2025)
Lately, buying and selling on credit is mostly done by the community. In the sale and purchase, the buyer will pay for the desired goods in installments with the agreed time limit. However, of course the price will be higher than paying in cash. The additional price is a problem among scholars. Some say it is haram, halal and even syuhbat. Apart from these differences of opinion, actually buying and selling (Taqsith) credit has benefits for both the seller and the buyer, namely the seller can make his merchandise sell quickly and the buyers can get the goods they want even though they do not have enough money to buy it. So that buying and selling credit can realize the benefit of the people. Several scholars from the Shafi'iyah, Malikiyah, Hanabilah, Hanafiyah schools and also Zaid bin Ali as well as the majority of scholars allow buying and selling with a credit system. As long as there is clarity during the buying and selling contract process. In determining Islamic law, the main reference sources are the Qur'an and al-Sunnah. The secondary source is the ijtihad of the scholars. Every istinbath (law-taking) in Islamic law must be based on the Qur'an and the Sunnah of the Prophet